Use of diatomaceous earth on intestinal transit time, apparent digestibility, bone morphometry and litter moisture of broilers - Verastegui Cordova, Fatima Valeria (2023)
The aim of this study was to evaluate the effects of diatomaceous earth (DT) supplementation in the diet of broiler chickens on intestinal transit time, apparent digestibility, bone morphometry and litter moisture. Two experimental trials were carried out with 220 male chickens and 220 female chickens, respectively, and with two treatments per trial: control treatment (without DT) and treatment with TD. Each treatment had 5 replicates and 22 chickens per replicate. The variables were evaluated at 21 and 42 days of age. Intestinal transit time increased (p<0.05) with the addition of DT in both stages and sexes, with a difference of 14.5 and 10.6 minutes in females and 34.5 and 22.2 minutes in males, respectively. Apparent protein digestibility increased (p<0.05) with DT supplementation at 21 and 42 days, and ash and calcium digestibility increased at 42 days. Litter moisture was decreased (p<0.05) in treatments with DT. The results indicate that the addition of DT can increase intestinal transit time, improve the digestibility of proteins, ash and calcium, and decrease litter moisture.